Solution-Processed Epitaxial Growth of MAPbI3 Single-Crystal Films for Highly Stable Photodetectors - Xu, Yubing; Wang, Xin; Zhao, Jingda; Pan, Yuzhu; Li, Yuwei; Elemike, Elias Emeka; Li, Qing; Zhang, Xiaobing; Chen, Jing; Zhao, Zhiwei; Akram, Javed; Bae, Byung Seong; et al. (Frontiers in Materials, 2021)
Recent years, organic-inorganic hybrid perovskites (OIHPs) have been widely used in applications, such as solar cells, lasers, light-emission diodes, and photodetectors due to their outstanding optoelectronic properties. Nowadays photodetectors based on perovskite films (PFs) suffer from surface and interface traps, which result from low crystalline quality of perovskite films and lattice mismatch between perovskite films and substrates. Herein, we fabricate MAPbI3 -(MA = CH3NH3) single-crystal films (SCFs) on MAPbBr3 single crystal substrates in MAPbI3 precursor solution during crystallization process via solution-processed epitaxy. Benefit from the good lattice matching, epitaxial MAPbI3 SCFs with high crystallinity and smooth morphology are of comparable quality to MAPbI3 PSCs and are of better quality than MAPbI3 polycrystalline films. Here we report that epitaxial MAPbI3 SCFs have a low trap density of 5.64×1011 cm–3 and a long carrier lifetime of 11.86 μs. In this work, photodetector based on epitaxial MAPbI3 single-crystal film (SCF) exhibits an excellent stability of a long-term stable response after 120 days, a fast response time of 2.21 μs, a high responsivity of 1.2 A W–1 and a high detectivity of 3.07 ×1012 jones.